WEO position statement on hygiene in digestive endoscopy: Focus on endoscopy units in Asia and the Middle East. Issue 1 (28th November 2016) - Murdani, Abdullah; Kumar, Ajay; Chiu, Han‐Mo; Goh, Khean‐Lee; Jang, Byung Ik; Khor, Christopher J. L.; Lau, James; Mostafa, Ibrahim; Ramchandani, Mohan; Ratanalert, Siriporn; Tajiri, Hisao; Yuen, Minghwa; et al.
Abstract : The aim of this position statement is to reinforce the key points of hygiene in digestive endoscopy. The present article details the minimum hygiene requirements for reprocessing of endoscopes and endoscopic devices, regardless of the reprocessing method (automated washer‐disinfector or manual cleaning) and the endoscopy setting (endoscopy suite, operating room, elective or emergency procedures). These minimum requirements are mandatory for patient safety. Both advanced diagnostic and therapeutic endoscopies should be carried out in an environment that is safe for patients and staff. Particular attention is given to contaminants. Procedural errors in decontamination, defective equipment, and failure to follow disinfection guidelines are major factors contributing to transmission of infection during endoscopy. Other important risk factors include inadequate cleaning, use of older endoscopes with surface and working channel irregularities, and contamination of water bottles or irrigating solutions. Infections by multidrug‐resistant organisms have become an increasing problem in health‐care systems worldwide. Since 2010, outbreaks of multidrug‐resistant bacteria associated with endoscopic retrograde cholangiopancreatography have been reported from the USA, France, Germany, and The Netherlands. In many endoscopy units in Asia and the Middle East, reprocessing procedures have lagged behind those of Western countries for cultural reasons or lack of financial resources. This inconsistency in standards is now being addressed, and the World Endoscopy Organization has prepared this position statement to highlight key points for quality assurance in any endoscopy unit in any country.